Simplifying
4x + -6y + -8 = 0
Reorder the terms:
-8 + 4x + -6y = 0
Solving
-8 + 4x + -6y = 0
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '8' to each side of the equation.
-8 + 4x + 8 + -6y = 0 + 8
Reorder the terms:
-8 + 8 + 4x + -6y = 0 + 8
Combine like terms: -8 + 8 = 0
0 + 4x + -6y = 0 + 8
4x + -6y = 0 + 8
Combine like terms: 0 + 8 = 8
4x + -6y = 8
Add '6y' to each side of the equation.
4x + -6y + 6y = 8 + 6y
Combine like terms: -6y + 6y = 0
4x + 0 = 8 + 6y
4x = 8 + 6y
Divide each side by '4'.
x = 2 + 1.5y
Simplifying
x = 2 + 1.5y